Reduced Citrate Synthase Activity Effect on Oxygen Consumption Rates in Isolated Mitochondria from Mice Liver and Muscles - Andrej Fokin; Rasa Žūkienė; Aivaras Ratkevičius (Lithuanian Sports University, 2018)
Background. Liver and skeletal muscles play the major role in metabolism. Mitochondria are of particular importance in functioning of these organs. We tested the hypothesis that reduced citrate synthase (CS) activity could induce improved fatty substrate and carbohydrate oxidation in mitochondria extracted from liver and hind limb muscles of mice. Methods. Eight mice each of 12-week-old control C57B6/J (B6) and congenic B6.A-(rs3676616-D10Utsw1)/ Kjn (B6.A) mice were studied. The mitochondria were isolated by differential centrifugation method followed by assessment of mitochondrial respiration and citrate synthase (CS) activity. Mitochondrial respiration was measured as oxygen consumption with Clark-type oxygen electrode by using polarography system. CS enzyme activity was measured spectrophotometrically. Results. The activity of CS was by ~32% lower for mitochondria for B6.A compared to B6 mice (603.9 ± 135.6 U/g and 894.2 ± 193.2 U/g, respectively). Mitochondrial respiration did not differ significantly between the strains. Conclusions. 30% reduction in citrate synthase activity does not impair mitochondrial respiration. Keywords:  mitochondrial respiration, insulin resistance, β-oxidation.